Markers and the Materno-Foetal Result of Caesarean Section: A Study at the Secondary Health Facility in Obudu, Cross River State, Nigeria - Maanongun MT; Ornguze AA; Ojabo AO; Eka PO (Medical Science: Recent Advances and Applications Vol. 3, 2025)
Background: Caesarean section (CS) refers to the delivery of a foetus, placenta and membranes after the age of viability through an abdominal and uterine incision. Caesarean section is further divided into two subtypes as far as the urgency of the operation is concerned. Elective caesarean section refers to those occasions where the decision to carry out caesarean section is made and planned more than 24 hours before delivery. Caesarean section (CS) is an important tool in obstetric care for the reduction of maternal and foetal morbidities and mortalities. This study was done to determine the CS rate, the indications and the maternal and foetal outcome of emergency and elective caesarean sections at the Sacred Heart Hospital Obudu, Cross River State. Methods: A retrospective review of clinical records of all patients delivered by CS from September 2011 to August 2016 at the Sacred Heart Hospital, Obudu, Cross River State, Nigeria was conducted. Data for the study were extracted from theatre records, labour ward records and neonatal ward records using a structured questionnaire. The information obtained included socio-demographic variables, obstetric history and outcome of caesarean section. The data collected was checked for its completeness, entered into a computer and analysed using SPSS version 20.0. Frequencies. Results: There were 2445 deliveries with 453 caesarean sections during the review period, giving a CS rate of 18.1%. Emergency CS accounted for 338(74.6%), while elective CS accounted for 115(25.6%). The main indications for emergency CS were cephalo-pelvic disproportion (CPD) (16.9%) and obstructed labour (16.0%), followed by breech deliveries. Previous CS was the main indication for elective CS (50.4%). Generally, the maternal and foetal outcomes of elective CS were better than emergency CS. There were 4 deaths, all accounted for by emergency CS, giving a CS mortality of 0.9%. Maternal morbidities like post-partum haemorrhage, sepsis, and prolonged hospital stay were worse among the emergency CS patients. Some conditions, like obstetric fistula and ruptured uterus, were found only amongst the emergency CS patients. For foetal outcome, poor Apgar score, sepsis, death, jaundice and need for referral were worse among emergency CS patients. Conclusion: The incidence of CS is high in this centre, with a higher rate of emergency than elective CS. Also, the maternal and foetal outcomes of emergency CS were worse than those of elective CS. Caesarean section remains an important tool in obstetrics practice for the reduction of maternal and neonatal morbidity and mortality. In this review, the main indications for emergency CS were CPD, obstructed labour and breech presentation, while previous CS was the main indication for elective CS.